Dignity, rank, and rights - Waldron, Jeremy; Dan-Cohen, Meir. (New York ; Oxford : Oxford University Press, 2012)
This volume collects two lectures by Jeremy Waldron that were originally given as Berkeley Tanner Lectures along with responses to the lectures from Wai Chee Dimock, Don Herzog, and Michael Rosen; a reply to the responses by Waldron; and an introduction by Meir Dan-Cohen.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Philosophical anthropology; Dignity; Civil rights; Human rights